Android-based Mobile Application with Rapid Application Development model for Village Administration Services - Johan, Fanny; Jansen Wiratama; Sunardi Oetama, Raymond; Ady Sanjaya, Samuel; Fernandi Wijaya, Santo; Sony Eko Nugroho, Antonius (The Indonesian Journal of Computer Science, 2023)
Village administration services are essential in a village's progress and villagers' satisfaction with village officials. There are many villages in Indonesia where services still need to be more optimal because they have limitations in disseminating information, unclear procedures, and the status of service applications that cannot be monitored. Mobile-based applications can optimize village administration services, which can bridge between villagers and village officials. From the results of several previous studies, the Rapid Application Development (RAD) model is relevant to be applied in designing Android-based village service applications with the Flutter framework. The SHA-512 algorithm is implemented to increase security by hashing passwords to strengthen database security in village service applications. The application produced in this research has been tested using the User Acceptance Test (UAT) method, and it was concluded that this system is suitable for use by villagers and improves Cihuni village services.